El período precrítico: su aporte - Mora Rodríguez, Arnoldo (2005)
This article intends to discuss Kant’s main points of view in his precritic period and, in essence, his critics to the rationalistic traditional metaphysics. The philosophy of Leibniz is the central objective of the critic of our author. Many quotations of Kant’s Trascendental Dialectics are also examined to demonstrate the weaknesses of the traditional rational philosophy.